Analysis of Interactive Learning Media in PAI Subjects at State Elementary School 050683 Tanjung Selamat Langkat - Usnaini Syahara; M. Farhan; M. Adly Amri; Diah Permata Sari; Efan Suhendi; Harmansyah Ramadhan (Jurnal Pendidikan Islam, 2025)
In today's digital era, the use of interactive learning media is an effective alternative to improve the quality of Islamic Religious Education learning in elementary schools. This study aims to analyze in-depth how the use of interactive learning media affects Islamic Religious Education subjects at SDN 050683 Tanjung Selamat Langkat. The method used is Qualitative with a descriptive approach and field research. In analyzing the data, the process is carried out with the steps of data reduction, data presentation, and concluding, by the Miles and Huberman qualitative data analysis model. The results of this study indicate that the use of interactive media in Islamic Religious Education (PAI) learning at SDN 050683 Tanjung Selamat Langkat has a significant impact on student engagement and understanding. This study also provides a new understanding that interactive media is not the only key factor for success. The success of Islamic Religious Education learning depends on the synergy between the media, the role of teachers, the readiness of facilities, school support, and the involvement of the students themselves.